CT-like images in MRI improve specificity of erosion detection in patients with hand arthritis: A diagnostic accuracy study with CT as standard of reference - Ulas, Sevtap Tugce; Ziegeler, Katharina; Richter, Sophia-Theresa; Ohrndorf, Sarah; Poddubnyy, Denis; Makowski, Marcus R.; Diekhoff, Torsten (RMD Open, 2022)
Objective To compare the diagnostic accuracy of susceptibility-weighted imaging (SWI), standard T1-weighted (T1w) images and high-resolution 3D-gradient echo sequences (volumetric interpolated breath-hold examination (VIBE)) for detection of erosions in patients with peripheral arthritis using CT as standard of reference. Materials and methods A total of 36 patients were included in the study. All patients underwent CT and MRI, including SWI, VIBE and T1w sequences of the clinically more affected hand. Two trained readers scored all imaging datasets separately for erosions in a blinded fashion. Specificity, sensitivity and diagnostic accuracy of MRI sequences were calculated on a per-patient level. Results CT was positive for erosion in 16 patients and 77 bones (Rheumatoid Arthritis MRI Score >0), T1w in 28 patients, VIBE in 25 patients and SWI in 17 patients. All MRI sequences performed with comparably high sensitivities (T1w 100%, VIBE 94% and SWI 94%). SWI had the highest specificity of 90%, followed by VIBE (50%) and T1w (40%). Both T1w and VIBE produced significantly higher sum scores than CT (341 and 331 vs 148, p<0.0001), while the sum score for SWI did not differ from CT (119 vs 148; p=0.411). Conclusion Specificity for erosion detection remains a challenge for MRI when conventional and high-resolution sequences are used but can be improved by direct bone depiction with SWI. Both T1w and VIBE tend to overestimate erosions, when CT is used as the standard of reference.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Arthritis; Arthritis; Magnetic resonance imaging; Rheumatoid